Genetic analysis of rice (Oryza sativa L.) genotypes for yield and nutritional quality characters - Farooq, MS Umar; Diwan, J R; Mahantashivayogayya, K; Kulkarni, Vikas V; Shakuntala, N M (ORYZA-An International Journal of Rice, 2019)
Micronutrient deficiency disorders are prevalent among the rice consuming  population and particularly poor people who are unable to afford nutrient rich supplementary food sources. The iron and zinc deficiency leads to crop yield losses as well as human health problems which is also known as "hidden hunger". Hence biofortification program has been initiated to identify varieties having high iron and zinc along with high yield. In the present study 46 rice genotypes along with 4 checks were received from IIRR, Hyderabad, India and were evaluated. Among various genotypes studied the promising genotypes with highest grain iron and zinc content along with higher yields and with intermediate amylose content were identified. The promising genotypes identified can be released to farmers after testing in multiplications for their stable performance or they can be used as parents in hybridization programme.